(untitled) (Journal of Pharma Insights and Research, 2026)
Urinary tract infections in the elderly population are significantly high due to physiological vulnerability and escalating antimicrobial resistance. Evaluation of 300 positive urine cultures from patients aged over 60 years in a South Indian tertiary care facility reveals a 30% isolation rate among suspected cases. Female predominance at 60% and a high prevalence in outpatient settings (85%) characterize the demographic distribution. Escherichia coli constitutes the primary uropathogen at 50%, followed by Klebsiella species at 16% and Enterococcus species at 10%. High resistance levels are observed in Escherichia coli against Ampicillin (93%), Amoxicillin-Clavulanic acid (80%), and Nalidixic acid (65%). In contrast, Meropenem, Piperacillin-Tazobactam, and Amikacin maintain superior sensitivity profiles. Klebsiella isolates exhibit significant resistance to Amoxicillin-Clavulanic acid at 88%, while Enterococcus species remain entirely susceptible to Vancomycin and largely responsive to Linezolid. The emergence of multidrug-resistant isolates in this demographic necessitates the implementation of localized antibiograms and stringent antimicrobial stewardship to mitigate risks of treatment failure. Targeted diagnostic methods and evidence-based therapeutic selection are essential to manage the complex interplay of immunosenescence and bacterial virulence factors in geriatric urology